If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6x + (-20) = 20 6x + -20 = 20 Reorder the terms: -20 + 6x = 20 Solving -20 + 6x = 20 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '20' to each side of the equation. -20 + 20 + 6x = 20 + 20 Combine like terms: -20 + 20 = 0 0 + 6x = 20 + 20 6x = 20 + 20 Combine like terms: 20 + 20 = 40 6x = 40 Divide each side by '6'. x = 6.666666667 Simplifying x = 6.666666667
| 4-3(3x+3)=5-4x | | 6-20=20 | | 6+(-20)=20 | | 50x^2-98x=0 | | (3z-u)(5z+5u)= | | 28/44 | | 502(x+3)+3.7(2-x)=3 | | 1/8*1/3=x | | (c^2+c-1)(c^2+7c-9)= | | 2x-3=-2x-7 | | 1/3+1/2=x | | 2h+9=61 | | (2-8i)(4+I)= | | f(x)=6x/5x-25 | | 6+(-20)=0 | | 6.15x+4=37.8225+2x | | 2r+8r+8=0 | | (8w)(4w^8z)(0)= | | 2x-3=12x-7 | | (-6+5i)-(7-5i)= | | 6.15+4=37.8225+2x | | 3y^3/4b^3y*10b^2/y | | 0=b^2-8b+115 | | h/9=64/72 | | 1/3*1/2=x | | 54=-2(1+4m)-4(1+3m) | | [v+2]-30=11 | | fx=21+20x-x^2 | | -7x+4(x+3)=39 | | 0.40=Log(y) | | [v+2]-30=-11 | | (20-x)+(2x-19)= |